Din eğitimi açısından Kur’an’da tövbe-istiğfarın süreç ve yapıları - Emanet, Sare (My University, 2011)
vbe, İstiğfar, Sosyal Süreç, Sosyalleşme ÖZET DİN EĞİTİMİ AÇISINDAN KUR’AN’DA TÖVBE-İSTİĞFARIN SÜREÇ VE YAPILARI Araştırmamız, bir önsöz, bir giriş, üç bölüm, sonuç ve bibliyografyadan oluşmaktadır. Girişte; araştırmanın konusu, amacı, önemi, iddia ve varsayımları, sınırları, yöntemi, ilgili literatür ele alınmış, araştırmanın kavramsal ve kuramsal çerçevesi çizilmiş, tövbe ve istiğfar kavramlarının etimolojik dinlerde ve dini ilimlerdeki yeri tartışılmıştır. Birinci bölümde; Kur’an’daki ayetler ile tövbe-istiğfar ele alınmıştır. İkinci bölümde; tövbeye yaklaşımlar başlığı altında, tövbe ve istiğfarın önemi, gerekliliği, esasları ve tövbenin psikolojik işlevleri anlatılmıştır. Üçüncü bölümde ise; dini sosyalleşme sürecinde tövbe ve istiğfar ele alınarak bölümün uygulamalı araştırma kısmında, Kuzey Kıbrıs Türk Cumhuriyeti’ndeki bir grup denek üzerinde yapılan mülakat tekniğine dayalı, tövbe ve istiğfara yaklaşımlar, deneysel olarak ölçülmüştür. Araştırma, sonuç ve bibliyografya ile son bulmaktadır. Repentance, Ask Forgiveness, Social Process, Socialization

THE CONCEPT OF REPENTANCE IN THE QURAN AND ITS REFLECTIONS IN RELIGIOUS EDUCATION The Study includes the preface, introduction, three sections, conclusions and bibliography. The introduction section deals with the topic of the study, the purpose of the study ,its significance , problem statement and its assumptions , limitations and delimitations of the study , the methodology , and the literature review . The conceptual and theoretical points of the study are considered and the role of the two concepts; “repentance” and “praying to God for forgiveness ” in etymological religions and religious science are discussed. In the first section “the verse of the Quran” and the two concepts; “repentance” and “praying God for forgiveness” are dealt with . The second section focuses on the importance of “repentance” and “praying God for forgiveness” , their necessity, their principles and the psychological functions of asking forgiveness. The third section analyzes the place of “repentance “ and “praying God for forgivenss” in the process of religious socialization. It also includes the interview carried out to evaluate the approaches of people to the process of repentance and asking forgiveness . The interview was carried out with a group of Turkish Republic of Northern Cyprus citizens. The conclusions and the bibliography are the following sections.
Keywords: Din Eğitimi; Kur’an-ı Kerim